Thyroid function in breast cancer patients - Ditsch, Nina; Liebhardt, Susanne; Koch, Franz Von; Lenhard, Miriam; Vogeser, Michael; Spitzweg, Christine; Gallwas, Julia; Toth, Bettina (Anticancer research, 2010)
Background: Recent studies indicate a possible relationship between hypothyroidism and breast cancer in vivo. In addition, oestrogen-like effects of thyroid hormones on breast cancer cell growth are seen in vitro. Therefore, this study evaluated thyroid function in breast cancer patients, women with benign breast tumour and healthy controls. Patients and Methods: Breast cancer patients (n=65), women with carcinoma in situ (n=13) or benign breast tumour (n=27), and healthy controls (n=38) were included in the study. Thyroid history was reported. Thyroid hormones (fT4, fT3, TSH) and thyroid antibodies (TPO, TRAK and TG) were determined. Statistical analysis was performed by Mann-Whitney U and Fisher's exact test (p<0.005 significant). Results: fT3 and fT4 levels were highest in breast cancer patients, and differed significantly from controls (fT3 and fT4: p<0.001) as well as from patients with benign breast tumour (fT3: p=0.021; fT4: p=0.017). TSH was highest in the control group without reaching significance. With regard to TRAK antibodies, breast cancer patients showed the highest levels differing significantly from women with benign breast tumours (p=0.048). Conclusion: Significant differences in fT3/fT4 as well as TRAK levels were observed among breast cancer patients, women with benign breast tumours and healthy controls. Further studies using larger patient groups are part of ongoing research.
Gesehen am 06.02.2023